Los prejuicios de clase y género: barreras en el acceso a la justicia para mujeres de estratos 0, 1 y 2 que fueron víctimas de violencia sexual (2020)
This research articulated part of the Marxist-feminist theory with the life experiences of more than 50 women who were victims of sexual violence. This, in the understanding that the discrimination and rejection that they experienced when trying to access justice has a historical basis related to power structures and the subordination of popular or subaltern social classes. The chosen sample is representative in that it reflects the reality of women who are located in seven territories of the country. According to the National Institute of Legal Medicine, the majority of women who report sexual violence live with the aggressor. Furthermore, in many of the cases the people who live with the victims do not have knowledge about their experiences and processes. -The articulating axis of my research was based on the life experiences and perceptions of the victims. This allowed me to contrast theoretical elements with the accounts of women who were victims of sexual violence in the armed conflict and who, furthermore, live in unfavorable economic conditions. The result, in addition to the body of this document, is an annex with proposals that will be presented to the Special Jurisdiction for Peace, in order to prevent and transform institutional practices harmful to the victims. In this sense, my research accounts for the structural and historical nature of the discriminations experienced by women in the seven selected regions of the country.